Reaksi Investor Terhadap Kinerja Keuangan Perbankan di Indonesia - Rasyidin, M.; Rizkina, Azka; Saleh, M. (TIN: Terapan Informatika Nusantara, 2023)
This study examines the reactions of investors in the stock market to the financial performance of banks in Indonesia. The data used for research is secondary data from banks listed on the Indonesia Stock Exchange. The data used is secondary data for 4 years (2019-2022). The method used is multiple regression analysis. The indicators used to measure banking financial performance are ROA (Return on Assets), Return on Equity (ROE) and Earnings per Share (EPS). The results of this study indicate that investors react negatively when there are changes in Return on Assets (ROA), but investors react differently when there are changes in Return on Equity (ROE) and Earnings per Share (EPS). The reaction to these two variables is positive, meaning that changes in ROE and EPS are responded positively by investors